An overall examination of the portrait of Maria Theresa from the collection of Jaroměřice nad Rokytnou Chateau - Machačko, Luboš; Háková, Jana (Univerzita Pardubice, 2020)
The important collection of baroque portraits, the so called Questenberg collection, at Jaroměřice nad Rokytnou Chateau in the Czech Republic is subject to conservation as well as a complex scientific investigation includ- ing a detailed material analysis. The portrait of Maria Theresa, one of many versions of Martin van Meytens’ portrait of the Holy Roman Empress Ma- ria Theresa, which was proliferated relatively soon after her father’s death, was one of the first paintings to be examined in detail and then restored. The condition of the painting, extent of damage, painting technique and type of materials used were identified by non-invasive (visible light – diffused/sharp oblique/translucent – photography, ultraviolet induced flu- orescence photography, infrared reflectography, X-ray radiography, X-ray fluorescence spectroscopy) and invasive techniques (optical microscopy, scanning electron microscopy, Fourier-transform infrared spectroscopy). Considerable changes to the composition during the execution of the por- trait was one of the most interesting findings as well as the identification of greasy tempera as a part of the painting technique, and identification of cotton fibres in the canvas. All of the above and much more recent infor- mation about the painting examined can be found in the following article.
Komplexní průzkum portrétu Marie Terezie ze sbírek zámku Jaroměřice nad Rokytnou
Keywords: examination; průzkum; conservation; technique of painting; pentimenti; konzervace; technika malby; pentimenti